Functional outcomes following pelvic exenteration: results from a prospective cohort study. (4th August 2021) - Makker, Preet G. S.; Koh, Cherry E.; Solomon, Michael J.; Ratcliffe, James; Steffens, Daniel
Abstract: Aim: Postoperative functional outcomes following pelvic exenteration surgery for treatment of advanced or recurrent pelvic malignancies are poorly understood. The aim of this study was to determine the short‐term functional outcomes following pelvic exenteration surgery using objective measures of physical function. Method: Patients undergoing pelvic exenteration surgery between January 2017 and May 2020 were recruited at a single quaternary referral hospital in Sydney, Australia. The primary measures were the 6‐min walk test (6MWT) and the five times sit to stand (5STS) test. Data were collected at baseline (preoperatively), 10 days postoperatively and at discharge from hospital, and were analysed according to tumour type, extent of exenteration, sacrectomy, length of hospital stay, major nerve resection and postoperative complications. Results: The cohort of patients that participated in functional assessments consisted of 135 patients, with a median age of 61 years. Pelvic exenteration patients had a reduced 6MWT distance preoperatively compared to the general population ( P < 0.001). Following surgery, we observed a further decrease in 6MWT distance ( P < 0.001) and an increase in time to complete 5STS ( P < 0.001) at postoperative day 10 compared to baseline, with a slight improvement at discharge. There were no differences in 6MWT and 5STS outcomes between patients based on comparisons of surgical and oncological factors. Conclusion: Pelvic exenteration patients are functionally impaired in the preoperative period compared to the general population. Surgery causes a further reduction in physical function in the short term; however, functional outcomes are not impacted by tumour type, extent of exenteration, sacrectomy or nerve resection.